Utility-based multicriteria model for evaluating BOT projects - Yan, Min-Ren; Pong, Cheng-Sheng; Lo, Wei (Technological and Economic Development of Economy, 2011)
Owing to the urgent demands for new developments and maintenances of the existing infrastructures under limited government budget and time, increasing BOT (build-operate-transfer) projects have been a significant factor affecting the economic developments in many countries. However, as BOT projects usually induce huge capital investments, government sectors must prudently evaluate the project feasibility from both financial and nonfinancial aspects before the implementation. Therefore, how to establish an objective evaluation model which can comprehensively assess the feasibility of each BOT project and determine the priority of its implementation has become an important issue. This study incorporates analytic hierarchy process (AHP) and utility theory to develop a utility-based multicriteria model for supporting the selection of BOT projects. A case study is provided to demonstrate that the implementation of the proposed model can effectively help decision-making teams participate in economical evaluations so that the feasibility of as-planed BOT projects can be determined and project priority can be set efficiently and consistently.Article in English.SEP projektų vertinimo modelis pagrįstas daugiakriterine naudingumo teorijaSantrauka. Dėl esamos infrastruktūros plėtros ir atnaujinimo būtinybės, esant ribotam valstybės biudžetui ir laikui, SEP (Statyba-Eksploatacija-Perdavimas) projektų vykdymas ženkliai prisidėjo prie daugelio šalių ekonominių pokyčių. Dažnai SEP projektai reikalauja didelių kapitalo investicijų, todėl valstybės sektorius turi įvertinti projekto įgyvendinimo galimybes tiek finansiniu tiek nefinansiu aspektu. Koks turi būti objektyvaus vertinimo modelis, kuris leistų visapusiškai įvertinti kiekvieno SEP projeto pagrįstumą ir nustatyti jo įgyvendinimo prioritetus? Šiame straipsnyje, naudojant analitinę hierarchinio proceso (AHP) struktūrą ir naudingumo teoriją, SEP projektų atrinkimui sukurtas daugiakriterine naudingumo teorija pagrįstas modelis. Skaitmeninis pavyzdys įrodo, kad siūlomas modelis gali sėkmingai pagelbėti atrenkant ekonomiškai efektyvius SEP projektus.Reikšminiai žodžiai: SEP projektai, naudingumas, AHP, daugiakriterinė analizė, įvertinimas, sprendimų parama.